Vpis slovenskih ledinskih in hišnih imen v seznam nesnovne kulturne dediščine Avstrije - Piko-Rustia, Martina (Etnolog. Nova vrsta (Ljubljana), 2018)
The article examines the case of the entry of Slovene fallow and house names from Carinthia in Austria's Register of Intangible Cultural Heritage to present, on the one hand, the effects and influence of UNESCO's Convention for the Safeguarding of the Intangible Cultural Heritage at the local level and, on the other hand, addresses the issue how local bearers of the intangible heritage contribute to the discourse at the national and international levels with their experiences. It is only when the bearers recognize their heritage as a value, that the heritage acquires value in the widest (international) environment.
Keywords: Avstrijci; hišna imena; ledinska imena; nesnovna kulturna dediščina; seznami; Unesco; zamejski Slovenci